Board features and their effects on financial performance: evidence from microfinance institutions in Cameroon - WOKWEN , Cordelia; NGOUNGOURE , Monta Maimouna; DAMARIS , Ning Mufur; PETER , Ngek Shillie; TAYONG , Desmond Mimba (Revue Internationale des Sciences de Gestion, 2023)
The aim of this paper is to analyse the effect that Board of Directors (BOD) features have on the financial performance of Microfinance Institutions (MFIs) in Cameroon. To achieve this goal, a quantitative approach was opted upon and data was collected from 130 category one MFIs in the towns of Bamenda, Bafoussam, Mbouda, Dschang, Buea, Limbe, and Douala of Cameroon using close-ended structured questionnaires. After analysis, the results showed that: the BOD size has a negative but insignificant effect on financial performance; the number of women in the BODs and BOD members’ competences have a positive and significant effect on financial performance; the number of BOD meetings has a negative and significant effect on financial performance. It is therefore recommended that the MFIs should strictly respect the norms put in place by the governing bodies and ensure the size of the BODs is sufficient enough to avoid conflicts and steady decision-making. They should try to institute a gender balance not forgetting competent members in their BODs.